Investigating the in situ degradation of atrazine in groundwater - Pearson, Robert; Godley, Andrew R.; Cartmell, Elise (Wiley, 2006)
This study focused on whether or not atrazine could be degraded by indigenous groundwater bacteria as part of an in situ remediation approach. Groundwater was taken from an unconfined middle upper chalk site where concentrations of atrazine and nitrate were typically in the ranges 0.02-0.2 µg litre-1 and 11.6-25.1 mg NO3-N litre-1 respectively. Sacrificial batch studies were performed using this groundwater spiked with atrazine at a concentration of 10 µg litre-1 in conjunction with a minimal mineral salts liquid (Glu-MMSL) medium which contained glucose as the sole carbon source. Treatments comprised either the Glu-MMSL groundwater cultured bacteria or Pseudomonas sp. strain ADP. Results from sacrificial batches indicated the occurrence of bacterial growth and denitrification as monitored by optical density (absorbance at 600 nm) and NO3-N content. Analysis of atrazine content by solid phase extraction coupled with high-performance liquid chromatography showed no degradation of atrazine over a period of 103 days in either treatment. These results indicated that no acclimatised bacterial community featuring positive degraders to the herbicide atrazine had become established within this chalk aquifer in response to the trace levels encountered. Copyright © 2006 Society of Chemical Industry.